(3GdeLjO aj EYQGH GdbQBf GdeLjOs - (3CHh ESMGb EHQGgje Hf eMeO GdUaGbSj,J (B742 (3g` s
(3ChdgG (B:s
(3EYQGH ShQI Hfi ESQGFjd SHMGf JbOe ai GdHbQI hRYe GdReNTQi Cfg Yde ddJSHjM cYKeGf Yde ddQLd bGd GHf YWjI hde jfUQa dCf ai BNQg Cda s
(3BNQgG (B:s
(3hCWdb Ydi GdLRA GSe GdfGS dCfge dGjJMQchf ai eQGOGJge hGdLf hGdLfI HeYfi bJjd ef GdLfI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B82s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1607s
Keywords: (3GdJaSjQ hYdhe GdbQBfs